2012
DOI: 10.1007/s10895-012-1143-0
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Co(III) and Ni(II) Complexes with Polypyridyl Ligands, [Co(phen)2(taptp)]3+ and [Ni(phen)2(taptp)]2+: Synthesis, Photocleavage and DNA-binding

Abstract: Two novel, mixed ligand complexes of cobalt(III) and nickel(II), [Co(phen) 2 (taptp)] 3+ (1) and [Ni(phen) 2 (taptp)] 2+ (2) (phen 0 1,10-phenanthroline and taptp 0 4,5,9,18-tetraazaphenanthreno [9,10-b]triphenylene), were synthesized and characterized by elemental analyses, UVvisible and NMR spectroscopies. The binding interactions of the two complexes with DNA have been investigated using absorption and emission spectroscopy methods and electrophoresis measurement mode. The intrinsic binding constants for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…2,13 Coordination of the biologically active organic molecules as ligands to the transition metal ions shows promise in this field because of their unique ability to bind different biological targets. 1,14 Some studies have recently found that polypyridyl complexes can function efficiently as electrochemical probes for nucleic acid sensing, particularly for CT-DNA, [15][16][17] as fluorescent probes for nuclear and protein components, 18 as DNA photocleavage agents, 19,20 or as catalytic inhibitors (or poisons) of human topoisomerase IIa. 19 They also display good binding propensity to transporting proteins, 21 and cytotoxicity against cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,13 Coordination of the biologically active organic molecules as ligands to the transition metal ions shows promise in this field because of their unique ability to bind different biological targets. 1,14 Some studies have recently found that polypyridyl complexes can function efficiently as electrochemical probes for nucleic acid sensing, particularly for CT-DNA, [15][16][17] as fluorescent probes for nuclear and protein components, 18 as DNA photocleavage agents, 19,20 or as catalytic inhibitors (or poisons) of human topoisomerase IIa. 19 They also display good binding propensity to transporting proteins, 21 and cytotoxicity against cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…1,14 Some studies have recently found that polypyridyl complexes can function efficiently as electrochemical probes for nucleic acid sensing, particularly for CT-DNA, [15][16][17] as fluorescent probes for nuclear and protein components, 18 as DNA photocleavage agents, 19,20 or as catalytic inhibitors (or poisons) of human topoisomerase IIa. 19 They also display good binding propensity to transporting proteins, 21 and cytotoxicity against cancer cell lines. 22 Terpyridine (tpy) and its derivatives are attracting considerable interest due to their ability to act as ligands in a wide range of transition metal complexes and DNA-binding agents.…”
Section: Introductionmentioning
confidence: 99%
“…11 In general, polypyridyl metal complexes displayed the intercalative binding modes to DNA for their large planar ligands and p-p overlapping interaction. 12,13 Over the past few decades, it has been considered that the polypyridyl metal complexes can probe nonradioactive nucleic acid and effectively cleave DNA. 14 In general, the DNA cleavage mode mainly contained oxidative cleavage, photocleavage and hydrolytic cleavage.…”
Section: Introductionmentioning
confidence: 99%